227k views
3 votes
Select the two values of x that are roots of this equation.
X2 + 2x - 5 = 0

User Betaorbust
by
5.9k points

1 Answer

3 votes

Answer:


x=-1+√(6 )


x=-1-√(6 )

Explanation:


x=\frac{-b±\sqrt{b^(2)-4ac } }{2a}

Ignore the A before the ±. It wouldn't let me type it correctly.

x² + 2x - 5 = 0

a = 1

b = 2

c = - 5


x=\frac{-2±\sqrt{2^(2)-4((1)(-5)) } }{2(1)}


x=(-2±√(4-4((1)(-5)) ) )/(2(1))


x=(-2±√(4+20 ) )/(2(1))


x=(-2±√(24 ) )/(2)


x=(-2±√((2)(12) ) )/(2)


x=(-2±√((2)(2)(6) ) )/(2)


x=(-2±√((2)(2)(2)(3) ) )/(2)


x=(-2±(√(2) )(√(2))(√((2)(3) )) )/(2)


x=(-2±2√(6 ) )/(2)

Two separate equations


x=(-2+2√(6 ) )/(2)


x=(-2-2√(6 ) )/(2)


x=-1+√(6 )


x=-1-√(6 )

User Jeff Hillman
by
5.6k points